Peran Unit Pengembangan Karir dan Kewirausahaan di Perguruan Tinggi (Studi tentang Proses Rekrutmen Tenaga Kerja melalui UPKK Universitas Brawijaya) - Dillah, Farah (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
The findings in the field shows that Unit Career Development and Entrepreneurship of UB (UPKK UB) held a recruitment process in two ways namely through campus hiring or hold a job fair. Companies that recruit prospective employees in the internal environment (campus hiring) Universitas Brawijaya is helped because to get human resources in accordance with the criteria of the company. In addition to campus hiringflagship programs and Entrepreneurship Career Development Unit of UB itself is organizing a job fair or commonly called the job market which is a container or where the labor force to seek and obtain information about job opportunities open and objective. Factors supporting the recruitment Unit Career Development and Entrepreneurship of UB consists of Bargaining Universitas Brawijaya, quality of alumni were nice, and a broad network while limiting factors are the weakness of the system information technology and the lack of making MoU (Memorandum of Understanding) among some faculty with industry within the internal scope of UB.